2014
DOI: 10.1186/1471-2431-14-185
|View full text |Cite
|
Sign up to set email alerts
|

Early maternal depressive symptoms and child growth trajectories: a longitudinal analysis of a nationally representative US birth cohort

Abstract: BackgroundMaternal depressive symptoms are negatively associated with early child growth in developing countries; however, few studies have examined this relation in developed countries or used a longitudinal design with data past the second year of the child’s life. We investigated if and when early maternal depressive symptoms affect average growth in young children up to age 6 in a nationally representative sample of US children.MethodsUsing data from 6,550 singleton births from the Early Childhood Longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 26 publications
7
42
0
Order By: Relevance
“…Grote et al, 14 in a study conducted in European countries, also found no differences concerning overweight or obesity comparing children exposed to maternal depression symptoms in the postpartum period with those not exposed. The same results were observed by Surkan et al, 2 in 2001, in a study carried out in the United States. In the unadjusted model, there was a statistically significant association, but after adjustment, the association was no longer sustained.…”
Section: Variables Psupporting
confidence: 88%
See 4 more Smart Citations
“…Grote et al, 14 in a study conducted in European countries, also found no differences concerning overweight or obesity comparing children exposed to maternal depression symptoms in the postpartum period with those not exposed. The same results were observed by Surkan et al, 2 in 2001, in a study carried out in the United States. In the unadjusted model, there was a statistically significant association, but after adjustment, the association was no longer sustained.…”
Section: Variables Psupporting
confidence: 88%
“…12 Studies suggest that this association is linked to a lack of maternal care and related to a deficient mother-child bond, low family support, precarious economic situation and local customs. 2,5,6,12,25 In rural Bangladesh, located in South Asia, Black et al, 26 detected, in 2009, the same results as in Pakistan. This study demonstrated that children of mothers with depression symptoms were almost twice more likely to be malnourished (OR= 2.17 95%CI= 1.24 -3.81, p=0.007).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations